Fishy business: regulatory and enforcement challenges of transnational organised IUU fishing crimes - Stefanus, Andrea A. (Trends in organized crime, 2021)
The article aims to find the answer on the main question of how can the criminalisation of IUU fishing, especially when committed by OCGs, under suppression conventions tackle the deficits of regulations and enforcement at the international and national levels? These deficits have origin in the limited prescription by international fisheries instruments and a large autonomy and discretion of states leading to substantive divergent policies, legal framework and practices at the national level. Further, the actual international fisheries instruments do not provide for regulatory and enforcement solutions in relation to the involvement of OCGs in IUU fishing. We argue that suppression conventions at global and regional levels could serve as solutions to supplement the deficits. In explaining the argument, first we examine the phenomenon of IUU fishing and its TOC dimensions, and the significant harms caused by it. Second, we examine the regulations and enforcement provisions of international and national fisheries instruments to establish the deficits. Third, we elaborate why suppression conventions are suitable solutions. Fourth, we analyse how suppression conventions can be regulated at global and regional levels in a way that they tackle the deficits. The results of this study can be used as a reference on how a transnational crime can be criminalised under suppression conventions both in terms of its reasonings and options and thus can contribute to the study of transnational criminal law. This study is important for transnational criminal law scholars, policy makers and practitioners in the field of enforcement.